Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Integrated Economic Equilibrium and Life Cycle Assessment Modeling for Policy‐based Consequential LCA - J. Mason Earles; Anthony Halog; Peter Ince; Kenneth Skog (Journal of Industrial Ecology, 2013)
Summary Consequential life cycle assessment (CLCA) has emerged as a tool for estimating environmental impacts of changes in product systems that go beyond physical relationships accounted for in attributional LCA (ALCA). This study builds on recent efforts to use more complex economic models for policy‐based CLCA. A partial market equilibrium (PME) model, called the U.S. Forest Products Module (USFPM), is combined with LCA to analyze an energy demand scenario in which wood use increases 400 million cubic meters in the United States for ethanol production. Several types of indirect economic and environmental impacts are identified and estimated using USFPM‐LCA. A key finding is that if wood use for biofuels increases to high levels and mill residue is used for biofuels and replaced by natural gas for heat and power in forest products mills, then the increased greenhouse gas emissions from natural gas could offset reductions obtained by substituting biofuels for gasoline. Such high levels of biofuel demand, however, appear to have relatively low environmental impacts across related forest product sectors.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Uses and Desirable Properties of Wood in the 21st Century - Theodore Wegner; Kenneth E. Skog; Peter J. Ince; Charles J. Michler (Journal of Forestry, 2010)
The desirability of specific wood properties is driven by a number of social, economic, and environmental factors that influence wood-use trends. This article discusses current continuing commercial uses of wood, significant new or emerging commercial uses, and desirable wood properties indicated by projected changes in wood use. Emerging issues and applications such as carbon markets/carbon sequestration, production of renewable energy, chemical feedstock production, and production of nano-enabled materials and products are expected to increasingly shape wood use as the 21st century progresses. However, current uses of wood are projected to remain the dominant uses for decades to come, and many desirable wood properties recognized as important to today's products will continue to be important. Projected expansion in US timber harvest will be matched by expansion of wood output from plantations. Advances in biotechnology will enable tailoring wood properties of plantation trees and short-rotation woody crops for specific end uses.

Abnormal blood flow in the sublingual microcirculation at high altitude - Daniel S. Martin; Can Ince; Peter Goedhart; Denny Z. H. Levett; Mike P. W. Grocott (European Journal of Applied Physiology, 2009)